MAQÄá¹¢ID AL-SYARÄªâAH AL-SYÄá¹¬IBÄª DAN AKTUALISASINYA DALAM NILAI-NILAI FALSAFAH PANCASILA - Ahmad, Agustan (State Institute of Islamic Studies (IAIN) Palu, 2011)
Allah swt. sent down the syarÄ«âah to mankind with certain purpose. The Â Â purpose ofÂ the syarÄ«âah is to provide benefit to mankind and prevent them from things that are not good. However, the Muslim scholars (ulamÄâ) have different understanding on the purpose of the syarÄ«âah and the procedures of its application. Therefore, the problem maqÄá¹£id al-syarÄ«âah become the object of a separate study in Islamic law. One of the Muslim scholars (ulamÄâ) who specifically discusses this issue is al-SyÄá¹ibÄ« in his book, al-MuwafaqÄt. This article deals withÂ maqÄá¹£id al-syarÄ«âahÂ of al-SyÄtibÄ« Â and its actualization in the philosophy valuesÂ of Pancasila.